(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: To estimate the current situation and correlation between burn out and work engagement of medical staff at Le Van Thinh Hospital in 2024. Method: A cross-sectional study was conducted in 152 health workers working at Le Van Thinh Hospital. Health workers were interviewed according to a set of pre-prepared structured questions after agreeing to participate in the study. Burn out scores were assessed using the MBI scale including 22 questions, work engagement scores were measured using the Vietnamese version of the (UWES-9). To analyze the relative importance of the influence of burn out and other related factors on health workers’ work engagement using the LMG method. Results: The average burn out score as assessed by medical staff is 42.22 ± 23.54/132 points. The average work engagement score of healthcare workers is 4.48 ± 0.99 points/6 points. Burn out, supervisor support, work unit and colleague support are important factors, contributing to explaining 34.2% of the influence on work engagement (R2 = 34.19%), in which work pressure has the highest influence at 59.5%. Conclusion: The higher the burn out, the lower the work engagement. Along with burn out, 3 factors including supervision and support from superiors, work unit and support from colleagues contribute to explaining more than 34% affects the work engagement of health workers. This is an important scientific basis to consider when proposing and making appropriate solutions and changes to improve the connection of healthcare workers with the hospital.